Implementasi Pembelajaran Bermuatan Computational Thinking Pada Materi Kegunaan Uang di Kelas III Sekolah Dasar - Fauziah Mas'ula Soffa; Anisa Sifa Yuginanda; Siti Luluk Saniyati; Kintan Limiansih (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2023)
This article describes learning that contains computational thinking (CT) on the use of money material in grade III elementary schools. CT is a basic skill that involves problem formulation, problem-solving, as well as scientific reasoning. The government's policy regarding the need to integrate CT into learning is motivated by the low-quality index of Indonesian education in PISA and efforts to prepare students for 21st-century skills. The material about the use of money has a special urgency, namely instilling financial literacy which can be beneficial for the future of students. The method used is descriptive qualitative with primary data sources, namely class III students at SD Negeri Jatisawit totaling 32 students. The results of this study are that the implementation of CT-charged learning on the use of money material can bring up CT foundational aspects, namely decomposition and algorithms, and the teacher's ability to manage computational thinking-charged learning on the use of money material reaches a score of 91.6 percent or in the "good" category, the results student learning achieved RTP in the high category, namely 85 percent on the decomposition foundation score and 88 percent on the algorithm foundation score, the student's response to the application of CT-loaded learning was positive by achieving a score of 88.75 percent. Artikel ini mendeskripsikan pembelajaran yang bermuatan computational thinking (CT) pada materi kegunaan uang pada kelas III sekolah dasar. CT adalah keterampilan dasar yang melibatkan perumusan masalah, pemecahan masalah, serta penalaran ilmiah. Kebijakan pemerintah mengenai perlunya pengintegrasian CT dalam pembelajaran dilatarbelakangi oleh rendahnya indeks mutu pendidikan Indonesia dalam PISA serta upaya mempersiapkan peserta didik menuju kecakapan abad 21. Materi kegunaan uang memiliki urgensi khusus yakni menanamkan literasi finansial yang dapat bermanfaat bagi masa depan peserta didik. Metode yang digunakan adalah kualitatif deskriptif dengan sumber data primer yakni peserta didik kelas III SD Negeri Jatisawit berjumlah 32 peserta didik. Hasil dari penelitian ini adalah bahwa implementasi pembelajaran bermuatan CT pada materi kegunaan uang dapat memunculkan aspek fondasi CT yakni dekomposisi dan algoritma, kemampuan guru dalam mengelola pembelajaran bermuatan computational thinking pada materi kegunaan uang mencapai skor 91,6 persen atau dalam kategori “baik”, hasil belajar peserta didik mencapai RTP kategori tinggi yakni 85 persen pada skor fondasi dekomposisi dan 88 persen pada skor fondasi algoritma, respon peserta didik terhadap penerapan pembelajaran bermuatan CT adalah positif dengan mencapai skor 88,75 persen.